Time to tell the truth - Parent, Nancy; Ibrahim, Dalia Mohamed; Maruyama, Jerrod (Giza, Egypt nahdet misr publishing house, 2021)
Morty, Mickey's nephew, learns that telling the truth is the right way to solve a problem, and not telling a lie
English stories
for child from 7 years to 10 years
Keywords: English stories